2018
DOI: 10.1093/eurheartj/ehy546
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in radiation exposure in cardiovascular computed tomography imaging: results from the PROspective multicenter registry on radiaTion dose Estimates of cardiac CT angIOgraphy iN daily practice in 2017 (PROTECTION VI)

Abstract: This large international radiation dose survey demonstrates considerable reduction of radiation exposure in coronary CTA during the last decade. However, the large inter-site variability in radiation exposure underlines the need for further site-specific training and adaptation of contemporary cardiac scan protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(114 citation statements)
references
References 28 publications
8
100
0
6
Order By: Relevance
“…However, lower kV acquisitions are becoming increasingly popular in order to reduce radiation and contrast medium volume. Recent results from the PROTECTION VI Study showed that low kV settings for cCTA (< 100 kV) are already applied in 14% of patients and this is only expected to increase [27,28]. Our results showed significant differences between all kV levels except between 80 and 90 kV, and between 100 and 120 kV.…”
Section: Discussionmentioning
confidence: 49%
“…However, lower kV acquisitions are becoming increasingly popular in order to reduce radiation and contrast medium volume. Recent results from the PROTECTION VI Study showed that low kV settings for cCTA (< 100 kV) are already applied in 14% of patients and this is only expected to increase [27,28]. Our results showed significant differences between all kV levels except between 80 and 90 kV, and between 100 and 120 kV.…”
Section: Discussionmentioning
confidence: 49%
“…37 Modern CTCA is an excellent test to non-invasively identify the presence of atherosclerosis in the coronary arteries at a low radiation dose. 38 The presence of CAD on CTCA has been linked to cardiac events in persons with diabetes, and conversely the absence of CAD on CTCA with a low event rate. 24,25,39,40 The FACTOR 64 RCT, which was underpowered due to fewer events than anticipated, did not find a benefit of using CTCA to screen participants with a mean diabetes duration of 12 years for CAD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For coronary CT angiography, the UK has the lowest international diagnostic reference levels set by Ionising Radiation (Medical Exposure) Regulations at 380 mGy.cm for retrospective acquisitions with ECG gating and 170 mGy.cm for prospective acquisitions with no padding 12. Focusing attention on the optimal scan acquisition in the field of coronary CT angiography has resulted in many centres switching from retrospective to prospective acquisitions and reducing tube current potential, thereby reducing the median radiation exposure by 78% 13 14. In this study, the wide variation in scanning techniques for acquiring CT-TAVI data sets would suggest that there is scope to lower radiation dose exposure through improved standardisation of practice across UK cardiac CT centres.…”
Section: Discussionmentioning
confidence: 99%